Baroque & Rococo - Gauvin A Bailey (Art & ideas., 2012)
'Baroque and Rococo' is a perfect detailed introduction to two styles of art, architecture and expression that bridged the Renaissance with the Enlightenment period. 'Baroque and Rococo' explores the key artists and works of the period, such as Rembrandt and Bernini, while expanding it's reach to include Asia and Latin America. 'Baroque and Rococo' contains excellent illustrations, maps, glossaries and biographies to capture the diversity of two art forms growing against the backdrop to a world of plague, war, rioting, rebellion and religious dissent. 'Baroque and Rococo' encompasses all arts - religious and profane painting and sculpture, church architecture and interiors, public buildings, palaces, domestic interiors, festivals, gardens, theatres, music, ceramics and furniture - to provide the reader with a thorough understanding of this great period in art history.